2012
DOI: 10.1371/journal.pone.0035952
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mowing on Methane Uptake in a Semiarid Grassland in Northern China

Abstract: BackgroundMowing is a widely adopted management practice for the semiarid steppe in China and affects CH4 exchange. However, the magnitude and the underlying mechanisms for CH4 uptake in response to mowing remain uncertain.Methodology/Principal FindingsIn two consecutive growing seasons, we measured the effect of mowing on CH4 uptake in a steppe community. Vegetation was mowed to 2 cm (M2), 5 cm (M5), 10 cm (M10), 15 cm (M15) above soil surface, respectively, and control was set as non-mowing (NM). Compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Similar with other studies all over the world (Dengel et al, 2011;Imer et al, 2013), the maximum uptake rate is usually observed in the afternoon due to the warmest soil condition during the day (Wang et al, 2003a;Du et al, 2005;Kato et al, 2013), except for a few reporting peak values at other times Dong et al, 2000;Qi et al, 2004). Typical seasonal patterns have been found in Inner Mongolia Wang et al, 1998Wang et al, , 2000Wang et al, , 2003aDu et al, 2005;Chen et al, 2010;Zhang et al, 2012) and on the Qinghai-Tibetan Plateau (Pei et al, 2003;Wang et al, 2009a), with larger uptake rates in summer and lower rates in winter (Liu et al, 2007;Holst et al, 2008;Chen et al, 2010 À1 based on 65 data) (P < 0.01), similar to the results of Wang et al (2005) due to warming condition in growing season enhancing activities of methanotrophs. The dominant factors for seasonal variation of CH 4 uptake are soil temperature and soil moisture (Jiang et al, 2010).…”
Section: Observed Ch 4 Uptakes In Grasslands In Chinasupporting
confidence: 69%
See 2 more Smart Citations
“…Similar with other studies all over the world (Dengel et al, 2011;Imer et al, 2013), the maximum uptake rate is usually observed in the afternoon due to the warmest soil condition during the day (Wang et al, 2003a;Du et al, 2005;Kato et al, 2013), except for a few reporting peak values at other times Dong et al, 2000;Qi et al, 2004). Typical seasonal patterns have been found in Inner Mongolia Wang et al, 1998Wang et al, , 2000Wang et al, , 2003aDu et al, 2005;Chen et al, 2010;Zhang et al, 2012) and on the Qinghai-Tibetan Plateau (Pei et al, 2003;Wang et al, 2009a), with larger uptake rates in summer and lower rates in winter (Liu et al, 2007;Holst et al, 2008;Chen et al, 2010 À1 based on 65 data) (P < 0.01), similar to the results of Wang et al (2005) due to warming condition in growing season enhancing activities of methanotrophs. The dominant factors for seasonal variation of CH 4 uptake are soil temperature and soil moisture (Jiang et al, 2010).…”
Section: Observed Ch 4 Uptakes In Grasslands In Chinasupporting
confidence: 69%
“…Thus, livestock grazing may have been the most important management of grasslands on both domains. Grazing was found to have complicated effects on CH 4 uptakes by grasslands, probably due to different grazing density and grazing patterns, or accompanied by difference of weather conditions and vegetation Wang et al, 2000;Wang et al, 2001Wang et al, , 2003bQi et al, 2003;Ma et al, 2006;Li et al, 2007;Liu et al, 2007Liu et al, , 2012cLin et al, 2009;Wan et al, 2010;Zhou and Hao, 2010;Zhou et al, 2011;Jiang et al, 2012;Zhang et al, 2012). In both semi-arid steppe ecoregion and alpine steppe and meadow ecoregion, the CH 4 uptake rate of freely grazed grasslands was lower than that of fenced grasslands (Table 1), partly due to grazing-induced changes in soil bulk density by tramping, soil nutrient and biomass allocation Qi et al, 2003;Wang et al, 2003b;Liu et al, 2007) based on 10 data).…”
Section: Observed Ch 4 Uptakes In Grasslands In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Soil temperature and moisture varied seasonally at this site (see Ref. [20]). Briefly, soil temperature at 5 cm depth ranged from 13.1˚C to 31.1˚C with an average of 22.3˚C in 2008, 8.5˚C to 27.9˚C with an average of 18.1˚C in 2009.…”
Section: Climatementioning
confidence: 96%
“…N 2 O reduction by denitrifying microorganism is associated with reduced levels of oxygen, which is usually related to increased moisture contents [26]. Despite the different patterns of N 2 O fluxes in July 2008 and 2009, soil moisture contents were not significantly different between these months [20]. Hence, unknown soil factors might have been responsible for the observed differences in the fluxes in July.…”
Section: Controls Of Changes In N2o Fluxesmentioning
confidence: 98%